Իրանահայութեան տեղաշարժերը և դրանց առանձնայատկութիւնները 21րդ դարի սկզբին - Մկրտչեան, Կարէն (տպ. Atlas)
The demographic problem caused by displacements has become a serious challenge for the Armenian community of Iran. For this reason, the community has decreased not only according to numerical indicators, but also in terms of various specialists. In addition, maintaining many other community structures, priority being given to educational centers and unions, has become an additional financial burden. Thus, Iranian Armenians entered the 21st century with major changes. The arrows of these shifts point westward to the US and the EU, as well as the developed Arab countries of the Gulf and Australia. One of the main features of the movements is that Iranian-Armenians are looking for an environment with better social and stable conditions. As a result, the social structure of the community has changed significantly; high-quality specialists and, especially, the number of young people have decreased. Under the new conditions, the maintenance of community structures, the priority being schools, which require large financial resources, has become problematic. The same applies to other structures, which have become few in number over time, and maintaining community institutions under these conditions has become a difficult task. Nevertheless, community structures continue to survive with the strength of tradition, and cultural associations continue to come up with various initiatives. Under the supervision of diocesan structures and two Armenian Members of Parliament in the Islamic Parliament, various social programs which have an Armenian-protecting significance are implemented.
Keywords: Հայ գաղթօջախներ; Իրանահայութիւն